Unit commitment in industrial microgrids with plug-in electric vehicles and photovoltaic generation - Derakhshandeh, S.; Masoum, Mohammad Sherkat; Hamedani Golshan, M. (John Wiley & Sons Ltd., 2015)
Summary Industrial microgrids (IMGs) consist of factories with distributed energy resources (DERs) and electric loads that heavily rely on combined heat and power (CHP) systems. The new generations of IMGs are expected to also include renewable DERs and plug-in electric vehicles (PEVs) with different power ratings and charging characteristics. This paper proposes a profit-based security constrained unit commitment (PB-SCUC) formulation for IMGs with PEV charging and renewable DERs that includes both microgrid security and factories constraints as well as the PEV charging requirements. PB-SCUC will utilize the generators waste heat to fulfill thermal requirements and also consider the status of renewable DERs to decrease the overall cost of IMG. To demonstrate the effectiveness of PB-SCUC, detailed simulation results are presented and analyzed for an IMG consisting of 12 factories and 6 types of PEVs without/with photovoltaic generations operating in grid-connected and stand-alone modes.